The Historical and Literary Context of Ateşten Gömlek’s Swedish Translation (Eldskjortan): The Translation Strategy, the Letters Between the Translator and Halide Edib, and the Reception of the Novel in Sweden - Ahmed Nuri (İstanbul Üniversitesi Edebiyat Fakültesi Türk Dili ve Edebiyatı Dergisi)
This article examines Halide Edib’s reception in Sweden through Eldskjortan (1928), the Swedish translation of her novel Ateşten Gömlek (1922) utilizing Swedish archives based on this translation. For this purpose, the article briefly addresses the first literary texts translated from Turkish to Swedish and discusses Eldskjortan within the context of this being the first text and novel translated from modern Turkish literature into Swedish. The second part of the article explores the translation strategy and process for Eldskjortan. This section includes the translator’s preface, the book’s appendix section, and the letters between the translator Hjalmar Lindquist and Halide Edib as found in the Swedish National Library. The final part of the article examines the reception of Eldskjortan and Halide Edib as an important figure in Turkish literature and history. The main sources of this reception are the articles, advertisements, and visuals in the Swedish press related to the novel, as well as writings about Halide Edib in Swedish books. In short, the article focuses on the historical and literary context of the Swedish translation of Ateşten Gömlek, presenting a new case for discussions on crossnational relationships and the recognition of female authors in Turkish literature. Moreover, the article contributes to Halide Edib’s biography, especially her years in exile, by providing new documents and information.